KCTD12 modulation of GABA(B) receptor function - Li, Melody (Pharmacol Res Perspect, 2017)
The molecular composition and functional diversity of native GABA(B) receptors (GABA(B)R) are still poorly understood, thus hindering development of selective GABA(B)R ligands. Potassium channel tetramerization domain‐containing protein (KCTD) 12 is a GABA(B)R auxiliary subunit and mouse KCTD12 can alter GABA(B)R function. In this study, we sought to characterize the effects of human KCTD12 on GABA(B)R kinetics and pharmacology, using an automated electrophysiological assay. Seizure susceptibility and ethanol consumption were also investigated in a KCTD12 knockout mouse model. Human KCTD12 co‐expression altered the kinetics of GABA(B)R‐mediated GIRK channels, speeding rates of both activation and desensitization. Analysis of concentration‐response curves showed that KCTD12 coexpression did not alter effects of the agonists GABA or baclofen on GABA(B)R. KCTD12 coexpression enhanced the potentiating effects of the positive allosteric modulator CGP7930, and its effects on GABA(B)R activation and desensitization. The function of KCTD12 in vivo was examined, using the KCTD12 knockout mouse model. The knockout mice were more resistant to a pentylenetetrazole proconvulsant challenge suggesting reduced seizure susceptibility. In the two bottle preference test, KCTD12 knockout mice demonstrated a reduced consumption at high ethanol concentrations. In summary, human KCTD12 accelerated the kinetics of GABA(B)R in vitro, in a manner possibly sensitive to allosteric pharmacological modulation. This study also provides novel in vivo evidence that the interaction between KCTD12 and GABA(B)R is of physiological significance, and may be a mechanism to more selectively modulate GABA(B)R.